PENGARUH DISTRIBUSI TULANGAN GESER TERHADAP KUAT GESER BETON RINGAN BUSA BERSERAT NYLON DENGAN METODE PUSH - OFF - Muhammad Ali Akoeb; Abdulah Abdullah (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2013)
This study aims to determine the effect of the distribution of shear reinforcement to shear strength fiber nylon foam lightweight concrete. Specimens used for testing the push - off is a Z - shaped concrete shear reinforcement that has been given by Av ( extensive reinforcement total ) = 113.08 mm2 , and a cylindrical specimen of 15 cm diameter and 30 cm high. Specimens were tested after the age of 28 days. The dimensions of the push - off test specimen is 20x10x30 cm. Push - off test specimens reinforced with 4Ø12 to avoid collapse in the neck specimen. Shear reinforcement placed according to the distance plans , and by means of welded dikat. Tests include lightweight concrete compressive strength test fiber foam, split tensile strength test of lightweight foam concrete fiber , steel tensile strength test to determine the quality of steel used, as well as lightweight foam concrete shear test berserat.Hasil testing shows the relationship between shear stress with tensile strength as well as strong he stressed. Vserat value ( shear stress due to the contribution of fiber ) used was 1.08 kg/cm2 and Vs ( shear stress due to the contribution of steel ) ) is 11.6 kg/cm2nilai contributions donated by the reinforcement fibers and obtained from previous studies . In this research also found the effect of reinforcing the widespread distribution of the total reinforcement ( Av ) is the sam . From these results obtained percentage value of shear stress against compressive strength with reinforcement 1Ø12 is 19.793 %, 25.574 % is 4Ø6 reinforcement , and 9Ø4 is 27.173 %. Difference in percentage of shear stress on split tensile strength is at 1Ø12 2.44% , 74.13 % and 85.21 % at 4Ø6 on 9Ø4 . Results shear push - off test specimen with reinforcement 1Ø12 is 49 250 kg/cm2, 4Ø6 is 55.470 kg/cm2 , and 9Ø4 is 59,000 kg/cm2 , it is known that the more the distribution of reinforcement will increase the shear stress fiber lightweight concrete foam .